Adjuvant therapy with GnRH agonists/tamoxifen in breast cancer should be a good council for patients with hormone receptor-positive tumours and wish to preserve fertility - Franco, J. G. [UNESP]; Oliveira, J. B. A. [UNESP]; Petersen, C. G. [UNESP]; Mauri, A. L.; Baruffi, R.; Cavagna, M. (Churchill Livingstone, 2012)
Infertility represents one of the main long-term consequences of the chemotherapy used for the adjuvant treatment of breast cancer. Approximately 60-65% of breast cancers express the nuclear hormone receptor in premenopausal women. Adjuvant endocrine therapy is an integral component of care for patients with hormone receptor-positive (HR+) tumours. The GnRH agonist (GnRHa) alone or in combination with tamoxifen produces results at least similar to those obtained with the different chemotherapy protocols in patients with HR+ breast cancer with respect to recurrence-free survival and overall survival. It is time to indicate adjuvant therapy with GnRHa associated with tamoxifen for patients with breast cancer (HR+ tumours) if they want to preserve their reproductive function. The evaluation of ovarian reserve tests: follicle stimulating hormone (FSH), anti-Mullerian hormone (AMH), inhibin B, antral follicle count (AFC) and ovarian volume 6 months, and 1 year after the end of therapy with GnRHa/tamoxifen must be realised. The recurrence-free survival and overall survival should be analysed. The major implication of this hypothesis will be to avoid adjuvant chemotherapy for patients with breast cancer (HR+ tumours) that request fertility preservation. It is expected that ovarian function should not be altered in almost all cases and subsequent pregnancy a real possibility. (C) 2012 Elsevier Ltd. All rights reserved.
A terapêutica adjuvante com agonista do GnRH/tamoxifeno no cancer de mama pode ser um bom conselho para os pacientes com tumors receptor-hormonal positivos e desejo de preservar a fertilidade